Genome‐wide association mapping of the architecture of susceptibility to the root‐knot nematode Meloidogyne incognita in Arabidopsis thaliana. Issue 2 (22nd February 2018) - Warmerdam, Sonja; Sterken, Mark G.; van Schaik, Casper; Oortwijn, Marian E. P.; Sukarta, Octavina C. A.; Lozano‐Torres, Jose L.; Dicke, Marcel; Helder, Johannes; Kammenga, Jan E.; Goverse, Aska; Bakker, Jaap; Smant, Geert
Summary: Susceptibility to the root‐knot nematode Meloidogyne incognita in plants is thought to be a complex trait based on multiple genes involved in cell differentiation, growth and defence. Previous genetic analyses of susceptibility to M. incognita have mainly focused on segregating dominant resistance genes in crops. It is not known if plants harbour significant genetic variation in susceptibility to M. incognita independent of dominant resistance. To study the genetic architecture of susceptibility to M. incognita, we analysed nematode reproduction on a highly diverse set of 340 natural inbred lines of Arabidopsis thaliana with genome‐wide association mapping. We observed a surprisingly large variation in nematode reproduction among these lines. Genome‐wide association mapping revealed four quantitative trait loci (QTLs) located on chromosomes 1 and 5 of A. thaliana significantly associated with reproductive success of M. incognita, none of which harbours typical resistance gene homologues. Mutant analysis of three genes located in two QTLs showed that the transcription factor BRASSINAZOLE RESISTANT1 and an F‐box family protein may function as (co‐)regulators of susceptibility to M. incognita in Arabidopsis. Our data suggest that breeding for loss‐of‐susceptibility, based on allelic variants critically involved in nematode feeding, could be used to make crops more resilient to root‐knot nematodes.